The 2006 IEEE International Joint Conference on Neural Network Proceedings 2006
DOI: 10.1109/ijcnn.2006.247106
|View full text |Cite
|
Sign up to set email alerts
|

Blur identification in image processing

Abstract: Abstract-The aim of this study is to achieve a blur identification task in still images. In fact, in photographic camera, the optical lenses may be set in a way to clearly distinct two areas in the image : the blurry one and the non blurry one. An automatic segmentation coupled to specific descriptors allow first to describe any region of the image. Then, a supervised learning processes permits to build a classifier able to decide for each unknown region the label "Blurry" or "Sharp". We discuss here precisely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Teo and Zhan 15 Liu et al 14 Xu et al 11 Rugna and Konik 13 Huang et al 18 Ours It is found that accuracy of these datasets is all greater than 94%, which again demonstrates our method has superior generalization ability and satisfactory robustness. Considering blurry images and sharp images separately, all precision and recall are greater than 94% except GoPro dataset.…”
Section: Methodsmentioning
confidence: 57%
See 2 more Smart Citations
“…Teo and Zhan 15 Liu et al 14 Xu et al 11 Rugna and Konik 13 Huang et al 18 Ours It is found that accuracy of these datasets is all greater than 94%, which again demonstrates our method has superior generalization ability and satisfactory robustness. Considering blurry images and sharp images separately, all precision and recall are greater than 94% except GoPro dataset.…”
Section: Methodsmentioning
confidence: 57%
“…Khan et al 12 proposed a blur discrimination method by frequency-based multi-level fusion transformation, which could detect and classify the blur and non-blur by single image processing. Rugna and Konik 13 observed that the blur was insensitive to low-pass filtering. They utilized this feature to judge whether a given image was blurry or not.…”
Section: Methods Based On Hand-extracted Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Aizenberg et al propose a neural network based on multivalued neurons to estimate the PSF [22,23]. Da Rugna and Konik present a supervised learning approach to classify the blurry and sharp regions in an image [24]. Some other techniques for blur identification include the methods based on the autoregressive model [25], kurtosis minimization [26], and the characteristics of the restored image [27].…”
Section: Introductionmentioning
confidence: 99%